Penentuan Lokasi Gudang Baru Untuk Meminimalkan Jarak Pengiriman Di PT. QRZ: Pusat Gravitasi - Taufik, Muh; Lahay, Idham Halid; Giu, Jamal Darusalam (Universitas Muhammadiyah Sorong, 2026)
PT. QRZ is a company located in Surabaya in the manufacturing industry selling iodized salt. This research aims to determine new warehouse location that are effective and efficient in minimizing transportation costs to distribution locations in Central Java. In current conditions with warehouses in Surabaya, the company's transportation costs are very high. This is caused by the shipping distance from the warehouse to the distributor, which is relatively far. This research uses the center of gravity and saving matrix method. The research using the center of gravity obtained the proposed location with coordinates (- 7.364217729, 110.488803), Kumpulrejo, Argomulyo Sub-district, Salatiga City, Central Java 50734. Analysis of the distance from the proposed warehouse using a saving matrix obtained a proposed location with a saving matrix of 38114.7 km. The proposed location can provide distance savings of 4,016.6 km, originally 8.372 km, оr get an efficiency of 47.98% and transportation costs of IDR 49,458,009, which means a reduction of 24.26%, initially IDR 65,301,600 per month.